2023
DOI: 10.3390/cancers15030765
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Prospects for Esophageal Cancer

Abstract: Esophageal cancer (EC) is the ninth most common cancer and the sixth leading cause of cancer deaths worldwide. Esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are the two main histological subtypes with distinct epidemiological and clinical features. While the global incidence of ESCC is declining, the incidence of EAC is increasing in many countries. Decades of epidemiologic research have identified distinct environmental exposures for ESCC and EAC subtypes. Recent advances in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 283 publications
0
38
0
1
Order By: Relevance
“…Malawi has the highest estimated incidence rate (17.5/100,000) of esophageal cancer in the world, with about 90% of cases being ESCC. 1,5,6 Most ESCC cases in Malawi present with advanced disease and patients typically die within a few months. Although ESCC is a very common cause of cancer death in Malawi, there has yet to be a systematic evaluation of its etiology or how to reduce its mortality burden in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malawi has the highest estimated incidence rate (17.5/100,000) of esophageal cancer in the world, with about 90% of cases being ESCC. 1,5,6 Most ESCC cases in Malawi present with advanced disease and patients typically die within a few months. Although ESCC is a very common cause of cancer death in Malawi, there has yet to be a systematic evaluation of its etiology or how to reduce its mortality burden in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Malawi has the highest estimated incidence rate (17.5/100,000) of esophageal cancer in the world, with about 90% of cases being ESCC 1,5,6 . Most ESCC cases in Malawi present with advanced disease and patients typically die within a few months.…”
Section: Introductionmentioning
confidence: 99%
“…1 The majority of EC cases are diagnosed at an advanced stage, with a five-year survival rate scarcely surpassing 40%. 2,3 Surgical intervention remains the primary course of treatment, and numerous studies have indicated that postoperative resection subsequent to neoadjuvant therapy can ameliorate the prognosis of patients with early-stage localized and metastatic EC. [4][5][6] In 2019, the National Comprehensive Cancer Network (NCCN) guidelines recommended that locally advanced EC patients could derive immense benefits from neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node (LN) metastasis and lung metastasis define clinical stages of malignancy. Although multimodal treatments including chemotherapy and radiation have improved prognosis of the ESCC patients considerably (Ando et al, 2012;Doki et al, 2022;Sheikh et al, 2023;van Hagen et al, 2012), the overall 5-year survival rate is Kohei Kemuriyama and Jianbo An contributed equally to this study. still low compared with other types of cancers, which underscores the importance of developing alternative therapeutic strategy for treating ESCC patients.…”
Section: Introductionmentioning
confidence: 99%